Inhibition of Ceramide De Novo Synthesis Ameliorates Diet Induced Skeletal Muscles Insulin Resistance - Krzysztof Kurek; Agnieszka Mikłosz; Bartłomiej Łukaszuk; Adrian Chabowski; Jan Górski; Małgorzata Żendzian-Piotrowska (Journal of Diabetes Research)
Nowadays wrong nutritional habits and lack of physical activity give a rich soil for the development of insulin resistance and obesity. Many researches indicate lipids, especially the one from the sphingolipids class, as the group of molecules heavily implicated in the progress of insulin resistance in skeletal muscle. Recently, scientists have focused their scrutiny on myriocin, a potent chemical compound that inhibits ceramide (i.e., central hub of sphingolipids signaling pathway) de novo synthesis. In the present research we evaluated the effects of myriocin application on type 2 diabetes mellitus in three different types of skeletal muscles: (1) slow-oxidative (red gastrocnemius), (2) oxidative-glycolytic (soleus), and (3) glycolytic (white gastrocnemius). For these reasons the animals were randomly divided into four groups: “control” (C), “myriocin” (M), “high fat diet” (HFD), “high fat diet” (HFD), and “high fat diet + myriocin” (HFD + M). Our in vivo study demonstrated that ceramide synthesis inhibition reduces intramuscular ceramide, its precursor sphinganine, and its derivatives sphingosine and sphingosine-1-phosphate concentrations. Moreover, FFA and TG contents were also decreased after myriocin treatment. Thus, myriocin presents potential therapeutic perspectives with respect to the treatment of insulin resistance and its serious consequences in obese patients.